Assessing the Involvement of Industries in Global Value Chains - Khaustova Viktoriia (EDP Sciences, 2021)
The purpose of the article is to assess the involvement of industries in global value chains and determine the prospects for intensification of these processes. The research methods are statistical analysis, comparison, graphical analysis. The role of export volumes of high value-added products, their enclosing in global value chains is determined. A methodical approach to assessing the involvement of industries in global value chains is proposed, allowing to detect the state of the country’s involvement in the international distribution of labour in concordance with specific industries. The analysis of the structure of exports of industries on the example of Ukraine is carried out. the industries that have a significant export share both in the total exports and in the structure of production output are determined. The leading indicators of the country’s involvement in global value chains are computed, as follows: the national added value in the country’s exports by industries, the contribution of specific industry sectors of the economy to the national added value of gross exports, the share of the national added value in exports of industries in the total national added value of gross exports. The positioning of industries within the coordinate system «share in the export structure - share of the national added value in exports» is carried out. It is determined that the share of national added value in exports of extractive industries of Ukraine is higher compared to the average of the world countries in this research. At the same time, being lower in the industries of the manufacturing industry, thus justifying the virtual absence of knowledge-intensive and innovative stages of production of the manufacturing industry, which necessitates a deeper specialization in the exports of low-grade products. The directions of a rational integration of the Ukrainian economy into global value chains are substantiated. The measures to be assumed on the part of the government policy to intensify the involvement of Ukrainian producers in global value chains are proposed.